How to read the first and last n rows of a file?

advertisements

I wonder how to read the first n lines and the last n lines of a file? For n=2, I read online that (head -n2 && tail -n2) would work, but it doesn't.

$ cat x
1
2
3
4
5
$ cat x | (head -n2 && tail -n2)
1
2

The expected output for n=2 would be:

1
2
4
5


Chances are you're going to want something like:

... | awk -v OFS='\n' '{a[NR]=$0} END{print a[1], a[2], a[NR-1], a[NR]}'

or if you need to specify a number and taking into account @Wintermute's astute observation that you don't need to buffer the whole file, something like this is what you really want:

... | awk -v n=2 'NR<=n{print;next} {buf[((NR-1)%n)+1]=$0}
         END{for (i=1;i<=n;i++) print buf[((NR+i-1)%n)+1]}'

I think the math is correct on that - hopefully you get the idea to use a rotating buffer indexed by the NR modded by the size of the buffer and adjusted to use indices in the range 1-n instead of 0-(n-1).

To help with comprehension of the modulus operator used in the indexing above, here is an example with intermediate print statements to show the logic as it executes:

$ cat file
1
2
3
4
5
6
7
8

.

$ cat tst.awk
BEGIN {
    print "Populating array by index ((NR-1)%n)+1:"
}
{
    buf[((NR-1)%n)+1] = $0

    printf "NR=%d, n=%d: ((NR-1 = %d) %%n = %d) +1 = %d -> buf[%d] = %s\n",
        NR, n, NR-1, (NR-1)%n, ((NR-1)%n)+1, ((NR-1)%n)+1, buf[((NR-1)%n)+1]

}
END {
    print "\nAccessing array by index ((NR+i-1)%n)+1:"
    for (i=1;i<=n;i++) {
        printf "NR=%d, i=%d, n=%d: (((NR+i = %d) - 1 = %d) %%n = %d) +1 = %d -> buf[%d] = %s\n",
            NR, i, n, NR+i, NR+i-1, (NR+i-1)%n, ((NR+i-1)%n)+1, ((NR+i-1)%n)+1, buf[((NR+i-1)%n)+1]
    }
}
$
$ awk -v n=3 -f tst.awk file
Populating array by index ((NR-1)%n)+1:
NR=1, n=3: ((NR-1 = 0) %n = 0) +1 = 1 -> buf[1] = 1
NR=2, n=3: ((NR-1 = 1) %n = 1) +1 = 2 -> buf[2] = 2
NR=3, n=3: ((NR-1 = 2) %n = 2) +1 = 3 -> buf[3] = 3
NR=4, n=3: ((NR-1 = 3) %n = 0) +1 = 1 -> buf[1] = 4
NR=5, n=3: ((NR-1 = 4) %n = 1) +1 = 2 -> buf[2] = 5
NR=6, n=3: ((NR-1 = 5) %n = 2) +1 = 3 -> buf[3] = 6
NR=7, n=3: ((NR-1 = 6) %n = 0) +1 = 1 -> buf[1] = 7
NR=8, n=3: ((NR-1 = 7) %n = 1) +1 = 2 -> buf[2] = 8

Accessing array by index ((NR+i-1)%n)+1:
NR=8, i=1, n=3: (((NR+i = 9) - 1 = 8) %n = 2) +1 = 3 -> buf[3] = 6
NR=8, i=2, n=3: (((NR+i = 10) - 1 = 9) %n = 0) +1 = 1 -> buf[1] = 7
NR=8, i=3, n=3: (((NR+i = 11) - 1 = 10) %n = 1) +1 = 2 -> buf[2] = 8